IMPLEMENTASI PENDAFTARAN MEREK SEBAGAI BENTUK PERLINDUNGAN HUKUM PADA UMKM DI KABUPATEN LANGKAT - Azfin Binti Zulfian, Fitria; Maryani, Halimatul; Sintara , Dani; Bakti Harahap, Syharul (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2025)
The rapid advancement of the economy and technology, particularly in business and marketing, has intensified competition, requiring Micro, Small, and Medium Enterprises (MSMEs) to seize opportunities creatively through unique trademarks and services. A trademark plays a vital role in distinguishing a product’s origin, quality, and authenticity. This study examines the implementation of trademark registration as legal protection for the Fitztox brand owned by MSME entrepreneurs in Langkat Regency. Using a normative legal research method based on existing laws and regulations, the study finds that registering the Fitztox trademark under PT Nada Mustika Abadi ensures exclusive rights and legal certainty. Conducted online through the MSME registration system, the trademark is protected for ten years (July 28, 2023–July 28, 2033) and can be renewed for another decade. Such protection not only safeguards brand identity but also enhances MSME competitiveness and sustainability in a dynamic market environment